Energy productivity through herbicidal weed control in soybean (Glycine max) - BILLORE, S D; JOSHI, O P; RAMESH, A (The Indian Journal of Agricultural Sciences, 2013)
Afield experiment was conducted during rainy season of 1996 and 1997 to study the energy productivity throughpost-emergence weedicides in comparision to pre-emergence and pre-plant incorporation weedicides and cultural practiceson soybean (Glycine max (L.)Merr.). Application of post-emergence weedicides (imazethapyr, propaquizafop andfenaxyprop-p-ethyl) were found equally effective in controlling weeds of soybean as pre-emergence (alachlor andpendimethalin), pre-plant incorporation (trifluralin) and 2 hand weedings as evidenced from the yield data. Applicationof anilophos followed by alachlor and 2 hand weedings consumed maximum energy input. The application of preemergenceand pre- plant incorporation weedicides was inferior to post-emergence weedicides with respect to energyoutput, energy-use efficiency, energy productivity and labour productivity. The weedy check and application ofanilophoswere the most energy intensive